Frequent Oomycotic Infections in Eggs of Cultured Species - Di Cesare, Luca Sebastian Guido (2023)
In aquaculture farms, incubation is a one crucial stage, as frequently shows high percentage of mortality. In fish and amphibians, egg oomycosis is a common infection during the early stages of embryonic development. Infection is usually promoted by unfertilized or damaged eggs that provide a medium for the zoospores to establish and grow, resulting in colonization and spread of the infection to nearby viable eggs. Numerous essential oils have been shown to have anti-oomycotic activity and to inhibit production and spore germination of Oomycetes species of the order Saprolegniales.